Descent trajectory modelling for the landing system prototype - Glaser-Opitz, Henrich; Labun, Ján; Budajová, Kristína; Glaser-Opitz, Leonard (Transport, 2020)
This paper gives another view on a method used for aircraft approach and landing phase of flight that enables replacement of standard glideslope. Proposed Landing System is based on Terrain Reference Navigation (TRN) using own created terrain elevation database, based on Radar Altimeter (RA) measurements compared to the overflown terrain. Simulations were performed on a chosen airport (KSC – Košice Airport) and aircraft (Boeing 737-800), where descend procedures was designed based on real airline data in compliance with Initial 4D Trajectory (i4D). Descend trajectory was modelled with EUROCONTROL Base of Aircraft DAta (BADA) performance model as a Continuous Descent Approach (CDA) from proposed merging point to the KSC RunWaY (RWY) threshold. This method was proposed to enhance pilot situational awareness in situations when standard Instrument Landing System (ILS) information could be lost or misleading and without the need of any ground station for successful navigation and guidance to the RWY threshold. Landing System prototype flight test were performed on full mission flight simulator.